Structure elucidation of laser dye coumarin-540A by joint application of X-ray diffraction, X-ray fluorescence, prompt fluorescence, UV and visible spectroscopy - KESKİN, SIDDIK SİNAN (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
X-ray, ultraviolet, and visible light induced photophysical changes of coumarin-540A in ethanol have been studied by the joint applications of X-ray, ultraviolet, and visible spectroscopy. Some impurities were found by X-ray fluorescence measurements. During the high power optical pumping, coumarin showed photochemical changes. Photoproduct emission spectra characteristics showed that photoproduct molecules can also be used as a laser dye at a different emission frequency in the ultraviolet region. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: laser dye; coumarin-540A; X-ray diffraction; X-ray fluorescence; absorption spectra; GAIN CHARACTERISTICS; INTENSITY; MOLECULES; STATE